2003
DOI: 10.1021/jp022517y
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Alkylammonium Ions in the Gas Phase

Abstract: Electrospray ionization-high-pressure mass spectrometry was used to determine the enthalpy, entropy, and Gibbs free energy for the equilibrium gas-phase ion-molecule association reactions of C m H 2m+1 NH 3 + (m ) 1-8), (CH 3 ) 2 NH 2 + , and (CH 3 ) 3 NH + with one to three water ligands. A subset of these ions has been studied previously, and the thermochemical properties determined in this investigation compare favorably with the previously published results, providing validation of our experimental techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…A weighted least-squares fit of the plots yields the thermochemical quantities for these systems listed in Table 2. Generally, the hydration enthalpies of the protonated amino acids and dipeptides obtained in the present work are similar to those found for a large number of protonated alkylamines whose values are in the range of 14-16 kcal/mol for the first, and 12-15 for the second water molecule (Table 1) [6,[9][10][11]17]. There is an obvious disagreement between the H • 0,1 and S • 0,1 values obtained in the present work and earlier data reported for ValH + , but good agreement in G • 0,1 ( Table 2) [14].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…A weighted least-squares fit of the plots yields the thermochemical quantities for these systems listed in Table 2. Generally, the hydration enthalpies of the protonated amino acids and dipeptides obtained in the present work are similar to those found for a large number of protonated alkylamines whose values are in the range of 14-16 kcal/mol for the first, and 12-15 for the second water molecule (Table 1) [6,[9][10][11]17]. There is an obvious disagreement between the H • 0,1 and S • 0,1 values obtained in the present work and earlier data reported for ValH + , but good agreement in G • 0,1 ( Table 2) [14].…”
Section: Resultssupporting
confidence: 87%
“…These systems were chosen because they have been well characterized by several investigators [9][10][11][12] and the results are of interest in connection with the hydration of the protonated amino acids and peptides. A comparison of the present results with previous measurements using the high-pressure mass spectrometric techniques with pulsed-electron [10,11] and ESI [9] ionization methods is shown in Table 1. The van't Hoff plot for the hydration of C 2 H 5 NH 3 + shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to ensure the aforementioned assumption approximately valid, we have to choose those amines with their alkyl chains long enough (containing four or more carbon atoms) to perform the competition experiments. Such a judicious choice is based on both the finding that the primary alkyl amines share a similar solvation energy when the number of carbon in the alkyl chain reaches four or larger, [33] and the notion that the solvation energy of the compound parallels its ion production rate according to the ion evaporation model of ESI, which is mainly accounted for the ionization of the small molecules. [34] In fact, Tang and Kebarle have reported that n-heptylamine and n-decylamine have nearly the same ESI-MS response because of their similar solvation energies.…”
Section: Theoretical Calculationsmentioning
confidence: 99%